The Political Economy of the Next Pandemic - van Bergeijk, Peter (Review of Economic Analysis)

(untitled) (International Centre for Economic Analysis, 2022)
While the COVID-19 pandemic and recovery unfold in real time, this article investigates some of the major themes on preparations for the next pandemic. Humanity cannot rely on modern medicine to beat the coming ‘disease X’ and the world cannot afford the extortionate health and economic policy interventions during the COVID-19 pandemic again. From the COVID-19 pandemic we learned that the international economic organizations suffered from disaster myopia and that the self-image of the advanced economies is distorted. It also has become apparent that ‘beggar-thy-neighbor’ health care was generally practiced while global health care should have been the norm. A discussion on the related issues of rationing, triage and scarcity of health care during a pandemic is urgently needed. All in all, a major global investment project is necessary to reduce the vulnerability to and impact of pandemics. As inequalities to a large extent determine pandemic vulnerability, an adjustment of Sustainable Development Goals (SDG) is necessary.